THE EFFECTIVENESS OF HYPNOTHERAPY-BASED EMOTIONAL FREEDOM TECHNIQUES ON INCREASING SELF-ESTEEM IN ADOLESCENTS EXPERIENCING BULLYING : SELF-ESTEEM - Kristia Novia; Euis Dedeh Komariah; Rosmina Situngkir; Karen Ambarita (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2026)
Background: Bullying experienced by adolescents can have a negative impact, particularly on self-esteem, which can hinder their psychological and social development. One of the psychological interventions needed is the Emotional Freedom Technique (EFT). This study aims to determine the effectiveness of EFT in improving self-esteem among adolescents who are victims of bullying. Methods: The study employed an experimental design using a pre-test post-test control group approach. The subjects of the study were adolescents identified as experiencing bullying. Results: The findings revealed a significant difference between the experimental group and the control group. In the experimental group, there was a significant increase in self-esteem following the EFT intervention, whereas the control group showed no change. Conclusion: The Emotional Freedom Technique is effective in enhancing the self-esteem of adolescent victims of bullying. The results of this study are anticipated to serve as a practical and straightforward alternative psychological intervention that can be implemented by health professionals and school counselors to assist adolescents in overcoming the negative effects of bullying.